Little Roja Riding Hood - Elya, Susan Middleton 1955-; Guevara, Susan (New York, NY : G.P. Putnam's Sons, an imprint of Penguin Group (USA), 2014)
A rhyming twist on the classic fairy tale in which a little girl saves her grandmother from a wolf. Includes glossary of the Spanish words sprinkled throughout the text.
Keywords: Fairy tales; Fairy tales; Folklore; Stories in rhyme; Spanish language materials -- Bilingual